Governance and Regional Development in Protected Areas of Switzerland and Austria - Pütz, Marco; Job, Hubert (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
The article investigates large protected areas from a governance research perspective. The analytical focus is on regional governance regimes of selected large protected areas in Austria and Switzerland. The analysis characterizes structures and patterns of regional governance regimes. Also, the kind and quality of cooperation between the actors is assessed. The article contributes to a deeper understanding of the regional governance of protected areas. Drawing from the empirical findings some recommendations are made for a more efficient management and organization of large protected areas.